Chinese cognitive processing of ToM: Distinctions in understanding the mental states of self, close others, and strangers - Wang, Yuanqing; Yuan, Xiaojing (Frontiers in psychology, 2023)
Previous studies showed that people differ in attributing mental states to themselves and in understanding the mental states of others, but have not explored the differences when people attribute mental states to others at different social distances. The present study adds a ‘close other’ condition to the Self/Other differentiation paradigm to explore the potential differences in attributing mental states to others with different social distances. It emerged that the time required to reflect on one’s self mental state is shortest in mental state attribution, longer when comprehending the mental state of close others, and longest for strangers. This result indicates that Chinese participants distinguish between close others and strangers when performing perspective-taking. When the perspective-shifting of belief-attribution is performed, a beforehand processing of information about close others or strangers does not interfere with the processing of information from oneself subsequently. However, when the information processed in the previous stage cannot be used for subsequent processing, it interferes with the processing of information from close others or strangers in the later stage. The lower the degree of automated processing of pre-processed information, the greater the interference effect produced. This finding indicated that processing the self mental state is automatically activated, but comprehending the mental state of others is not. The comprehension of others’ mental states occurs only when required by the task and it entails more cognitive resources to process and maintain.